Clinical Profile and Management of Peritonsillar Abscess in a Sub Saharan Africa - Adegbiji, Waheed Atilade; Olajide, Gabriel Toye; Adebayo, Aluko AbdulAkeem (International Journal of Innovative Research in Medical Science, 2020)
Background: Peritonsillar abscess is a common pathology that presents to an otolaryngologist with poor documentation especially in developing countries. The aim of this study was to describe the clinical profile and management of peritonsillar abscess in our practice. Material and Method: This was a retrospective study of patients presenting to our Ear, Nose and Throat facility with diagnosis of peritonsillar abscess. Information obtained includes detailed demographic characteristics, clinical findings and management of the patients. All obtained data were collated, entered into computer system and analyzed using SPSS version 18.0. Results: Prevalence of peritonsillar abscess was 0.2%. There were 38.9% males and male to female ratio was 1:1.6. Duration of illness at presentation with more than 1 week was 75.9% and single episode occurred in 85.2%. Right peritonsillar abscess accounted for 66.7% and aspirated pus of more than 5 ml was recorded in 48.1%. Majority (87.0%) of the patients was referred and 42.6% of such referral is by family physician. Patients seen in ear, nose and throat outpatient clinic were 83.3%. Common symptoms at presentation were fever, sore throat, odynophagia and otalgia in 100%, 94.4%, 90.7% and 59.3% respectively. All the patients (100%) had enlarged tonsils and with deviated uvula on clinical examination followed by 98.1% exudate on the tonsils and 31.5% trismus. Test aspirate confirmed peritonsillar abscess in 68.5% and all revealed growth of bacteria. Common isolated bacteria were 35.2% Streptococcus species and 11.1% Staphyloccocus aureus. Isolated Streptococcus species and Staphylococcus aureus had 100% sensitivity to cefuroxime, gentamicin, azithromycin, ceftazidine, Amoxicillin and Streptomycin. Prior prehospital treatment was received by 81.5% patients. Hospital treatments were surgical intervention and medical treatment in 90.7% and 100% respectively. Recurrences occurred in 3.7% during followed up. Conclusion: Peritonsillar abscess are common disorder with female preponderance in this study. The prevalence recorded in this study was 0.2%. It usually mimic other causes of fever hence eye index of suspicion is essential. Surgical treatment remains the effective mode of management in our study.